Pengaruh Penambahan Sari Lemon Cina (Citrus miceocarpa) Terhadap Karakteristik Fisikokimia Dan Organoleptik Hard Candy Pala (Miristica fragrans Houtt) - Indriyani, Haedar K; Ega, La; Breemer, Rachel (Jurnal Agrosilvopasture-Tech, 2024)
Developing nutmeg juice and Chinese lemon juice into hard candy is one of the efforts to increase the economic value of nutmeg juice and Chinese lemon juice. This study aims to determine the concentration of Chinese lemon juice on the physiological and organoleptic hard candy nutmeg. This study used RAL with one factor, namely concentration comparisons of Chinese lemon juice with five levels of treatment: 100%:0%, 95%:5%, 90%:10%, 85%:15%, and 80%:20%. The parameters observed include water content, ash content, vitamin C, total acid, sugar reduction, and sensory tests, including color, taste, aroma, and texture. The result of the hard candy study with the treatment of 20% Chinese lemon concentration was the best treatment based on chemical characteristics, including water content 2,55%, ash content 0,46%, vitamin C 0,04%, total acid 74,4%, pH 3,35%, sugar reduction 6,79%. In contrast, the organoleptic test characteristics include color 2,74 (brown), taste 2,42 (Chinese lemon taste), aroma 1,96 (Chinese lemon aroma), texture 2,34 (hard), and overall 2,90 (like), and based on the hard candy quality standard SNI 3547.1;2008 20% is a treatment that meets quality standards.